The Effect of Social Development and Government Support on Social Quality of Rural Comunities in Baling, Kedah - Abdul Azeez, Abdul Rahim (2023)
Despite the progress made in improving social quality in Malaysia, there are still several challenges and issues that need to be addressed. Some of the key problems include income inequality, ethnic and religious tensions, limited political freedom, environmental degradation and access to health and education. The main aim of this study is to identify the social quality among rural communities residing at Baling in Kedah, Malaysia. This quantitative study used a constructed questionnaire as main tool to collect data on the social quality of the rural communities. There are 363 number of sample size using stratified random sampling technique on the selection of respondents based on the 600 distributed and 400 collected questionnaires. The findings showed that the social quality is most directly influenced by the characteristics of social development indicators; social economic security, social cohesion, and social inclusion, with government support acting as a major mediator and having a considerable impact. In order to improve the social quality of these rural communities in Baling and duplicate them in other parts of Malaysia, recommendations are made in the hopes that the findings will be helpful for developing solutions.